L’IUS GENTIUM romano come ordinamento transnazionale - Giliberti, Giuseppe (Cultura giuridica e diritto vivente, 2015)
[The Roman ius gentium as transnational law] According to this research international law is a phenomenon much older than the Treaty of Westfalia. The 'international community' comes into existence whenever the actors of international relations accept to be limited by binding rules based on reciprocity. These conditions existed in several historical periods, in Antiquity and in the Middle Ages. In particular, the ius Fetiale and the ius gentium played the role of public international law when the Roman Republic became the ruling power of the Mediterranean area. Ius gentium, which was at the same time public and private, can be termed a transnational law. It was also a special branch of civil law influenced by the Mediterranean "lex mercatoria". Its rules and procedures were accessibile, with the permission of the praetor, by both Romans and foreigners.